Respuesta :

Answer:

y = - 3x + 6

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

Rearrange x - 3y = 5 into this form

Subtract x from both sides

- 3y = - x + 5 ( divide all terms by - 3 )

y = [tex]\frac{1}{3}[/tex] x - [tex]\frac{5}{3}[/tex]  ← in slope- intercept form

with slope m = [tex]\frac{1}{3}[/tex]

Given a line with slope m then the slope of a line perpendicular to it is

[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{\frac{1}{3} }[/tex] = - 3

Note the line crosses the y- axis at (0, 6) ⇒ c = 6

y = - 3x + 6 ← equation of perpendicular line